Introducing the Oxford Vocal (OxVoc) Sounds database: a validated set of non-acted affective sounds from human infants, adults, and domestic animals - Parsons, Christine E.; Young, Katherine S.; Craske, Michelle G.; Stein, Alan L.; Kringelbach, Morten L. (Frontiers in Psychology, 2014)
Sound moves us. Nowhere is this more apparent than in our responses to genuine emotional vocalizations, be they heartfelt distress cries or raucous laughter. Here, we present perceptual ratings and a description of a freely available, large database of natural affective vocal sounds from human infants, adults and domestic animals, the Oxford Vocal (OxVoc) Sounds database. This database consists of 173 non-verbal sounds expressing a range of happy, sad, and neutral emotional states. Ratings are presented for the sounds on a range of dimensions from a number of independent participant samples. Perceptions related to valence, including distress, vocalizer mood, and listener mood are presented in Study 1. Perceptions of the arousal of the sound, listener motivation to respond and valence (positive, negative) are presented in Study 2. Perceptions of the emotional content of the stimuli in both Study 1 and 2 were consistent with the predefined categories (e.g., laugh stimuli perceived as positive). While the adult vocalizations received more extreme valence ratings, rated motivation to respond to the sounds was highest for the infant sounds. The major advantages of this database are the inclusion of vocalizations from naturalistic situations, which represent genuine expressions of emotion, and the inclusion of vocalizations from animals and infants, providing comparison stimuli for use in cross-species and developmental studies. The associated website provides a detailed description of the physical properties of each sound stimulus along with cross-category descriptions.